Alginate Oligosaccharide Ameliorates D-Galactose-Induced Kidney Aging in Mice through Activation of the Nrf2 Signaling Pathway. (9th January 2021) - Pan, Hui; Feng, Wenjing; Chen, Ming; Luan, Hong; Hu, Yi; Zheng, Xiaoyue; Wang, Shan; Mao, Yongjun
Abstract : Aging is an independent risk factor for the development of age-related progressive kidney injury. As a part of the aging process, kidney aging has been indicated to be associated with oxidative stress-induced damage. Ameliorating oxidative damage is therefore considered a promising strategy for delaying kidney aging. Alginate oligosaccharide (AOS) has been reported to have a wide range of biological and pharmacological activities. However, no studies have focused on the role of AOS in delaying the kidney aging process. In this study, we aimed to evaluate the potential effects of AOS on kidney aging and its possible mechanisms. Subcutaneous injection of D-galactose (D-gal) (200 mg·kg -1 ·d -1 ) in C57BL/6J mice for 8 weeks was used to establish the aging model. AOS (200 mg·kg -1 ·d -1 ) was administered via oral gavage for the last four weeks. As a result, AOS inhibited the D-gal-induced upregulation of aging markers and significantly improved the kidney index and kidney function of D-gal-induced mice. In addition, AOS ameliorated the degree of tissue damage and fibrosis in the aging kidney. To further explore the potential mechanisms by which AOS attenuates the kidney aging process, the associated oxidative stress-induced damage was analyzed in depth. The data showed that AOS upregulated the expression of Klotho and decreased malondialdehyde levels by increasing the expression of antioxidant enzymes. Furthermore, our results suggested that AOS activated the nuclear factor erythrogen-2 associated factor 2 (Nrf2) pathway by promoting Nrf2 nuclear translocation in aging mice and upregulated the downstream expression of heme oxygenase-1 (HO-1) and NADPH quinone oxidoreductase 1 (NQO1). In conclusion, the present study demonstrated that AOS is a promising agent for attenuating kidney aging, and the underlying molecular mechanisms are related to the activation of the Nrf2 signaling pathway.